2009
DOI: 10.1016/j.jcrs.2008.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure assessment in both eyes of the same patient after laser in situ keratomileusis

Abstract: The IOP measurement reduction after LASIK was greater in cases of higher preoperative IOP and smaller in cases of lower preoperative IOP. The IOP measurements after LASIK were not significantly associated with laser ablation depth, and the measurements were similar and proportional in eyes of the same patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[17][18][19] In some cases, the magnitude of change in IOP might be disproportional to ablation depth after refractive surgery. 20 Our results indicate that GAT, NCT, and Tono-Pen correlate positively with CCT, but DCT readings do not. This finding is consistent with previous reports that DCT readings are not significantly associated with CCT.…”
Section: Discussionmentioning
confidence: 51%
“…[17][18][19] In some cases, the magnitude of change in IOP might be disproportional to ablation depth after refractive surgery. 20 Our results indicate that GAT, NCT, and Tono-Pen correlate positively with CCT, but DCT readings do not. This finding is consistent with previous reports that DCT readings are not significantly associated with CCT.…”
Section: Discussionmentioning
confidence: 51%
“…However, the LASIK with femtosecond laser changed not only the corneal thickness but also the overall eye structure. 27 Previous studies show that a larger myopic correction correlates with a larger decrease in CH and CRF. 12,29 Accordingly, the lower preoperative MRSE influenced the corneal biomechanical metrics as well as the corneal thickness.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies suggest factors that predict change in IOP measurements after LASIK with microkeratome for flap creation. 12,27 Qazi et al 12 showed that residual stromal bed and the ratio of flap thickness to preoperative CCT predict the percentage change in IOPg and that flap thickness and AD predict the percentage change in GAT. However, these authors identified no variable that predicts the percentage change in IOPcc.…”
Section: Discussionmentioning
confidence: 99%
“…We have now shown that overnight orthokeratology also results in a decrease in IOP as measured with an NCT, most likely because of the associated decrease in CCT. In general, the decrease in CCT associated with orthokeratology is 10-20 lm [10,[13][14][15][16][17], which is smaller than the changes induced by LASIK (80-100 lm) [21][22][23]. One view is that the refractive changes induced by overnight orthokeratology are predominantly attributable to the thinning of the corneal epithelium [13], which may not affect corneal rigidity.…”
Section: Discussionmentioning
confidence: 98%